Diabetes morbidity after displacement - Annette Bergemann; Erik Grönqvist; Soffia Guðbjörnsdóttir (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2018)
We investigate how career disruptions in terms of job loss may impact morbidity for individuals diagnosed with type 2 diabetes (T2D). Combining unique, high-quality longitudinal data from the Swedish National Diabetes Register (NDR) with matched employer-employee data, we focus on individuals diagnosed with T2D, who are established on the labor market and who lose their job in a mass layoff. Using a conditional Difference-in-Differences evaluation approach, our results give limited support for job loss having an impact on health behavior, diabetes progression and cardiovascular risk factors.
Keywords: J63; I14; I10; 330; Job displacement; Health; Diabetes; Unemployment